Product-Relationship-Matrix Concept for Marine and Fishery Supply Chain Model Development - Widodo, Kuncoro Harto; Perdana, Yandra Rahadian; Sumardjito, Joewpno (Jurnal Teknologi Pertanian, 2011)
Indonesia, as an archipelago country has the resources of marine and fisheriesboth in terms of its quantity and diversity. Currently the demand of fisheries productscontinue to increase. This is an opportunity for Indonesia to be able to utilize theeconomic potential as a competitive advantage lies in the mechanism or how to regulatethe flow of marine and fishery products in a supply chain. Therefore, this paper aims topropose a concept of Product-Relationship-Matrix for the development of supply chainmodels of marine and fishery. This model is expected to support the development ofeconomic and the well-being of marine and fishery businesses community, both in small,medium and large scale.KeywordsÂ : Supply chain, Product-Relationship-Matrix, marine and fishery products.